The effectiveness of combined anaerob-aerob biofilters and phytoremediation using Eichhornia crassipes for reducing ammonia and TSS content in noodle industry liquid waste - Zubaidah Zubaidah; Sampe Harahap; M. Hasbi M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The noodle industry liquid waste is rich in ammonia and TSS and thus need to be processed before being flown to environment. A research aims to reduce the ammonia and TSS on liquid waste using biofilters has been conducted in March-April 2018.The noodle industry liquid waste (175 liters) wastreated using a batch system that was consisted of2 anaerob and 1 aerob tanks and Eichhrornia crassipes phytoremediation pond. The liquid waste was kept for 10 days in anaerob tank with gravel, sand and fibers media. Then the waste was kept for 7 days in aerob tanks with mangrove charcoal media.Finally the waste was kept for 15 days in a phytoremediation pondthat was completed with Eichhrornia crassipes. By the end of the experiment, the ammonia reduced from 9.123 mg/L to 0.415 mg/L (effectiveness 95.45%)and TSS reduced from 448 mg/L to 85 mg/L (effectiveness 81.02%). The treated waste was used for rearing Cyprinus carpio L. fingerling (4 - 7 mm TL) for 15 days and survival rate of the fish was 85%. Based on data obtained, the combination of anaerob-aerob biofilters and phytoremediationusing Eichhornia crassipes is effective to reduce the ammonia and TSS content in thenoodle industry liquid waste.Keywords: Mangrove charcoal, Organic waste, organic pollutant, waste water, batch system